Question-6
Let \(a\) and \(b\) be two vectors. Compute the following:
\(3(a+b)+[(a+b)-(a-b)]\)
\(5(a+b)-[(a+b)-(a-b)]\)
\(3(a+b)+[(a+b)+(a-b)]\)
\(5(a+b)-[(a+b)+(a-b)]\)
First:
\[ \begin{aligned} 3(a+b)+[(a+b)-(a-b)] & =3a+3b+(a+b-a+b)\\ & =3a+3b+2b\\ & =3a+5b \end{aligned} \]
Second:
\[ \begin{aligned} 5(a+b)-[(a+b)-(a-b)] & =5a+5b-(a+b-a+b)\\ & =5a+5b-2b\\ & =5a+3b \end{aligned} \]
Third:
\[ \begin{aligned} 3(a+b)+[(a+b)+(a-b)] & =3a+3b+2a\\ & =5a+3b \end{aligned} \]
Fourth:
\[ \begin{aligned} 5(a+b)-[(a+b)+(a-b)] & =5a+5b-2a\\ & =3a+5b \end{aligned} \]